2022
DOI: 10.1039/d1md00392e
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of novel microtubule suppressors with an imidazopyridine scaffold through structure-based virtual screening and docking

Abstract: Targeting the colchicine binding site of α/β tubulin microtubules can lead to suppression of microtubule dynamics, cell cycle arrest and apoptosis. Therefore, the development of microtubule (MT) inhibitors is considered...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The relation between potency, pharmacokinetics, and toxicity is very crucial for the drug efficiency. Using pkCSM [48], Swiss ADME [49], and Data Warrior [48,50], the pharmacokinetics (absorption, distribution, metabolism, and excretion), drug-likeness, and toxicity features of the chemical compound 8 were assessed in this investigation. For a medicine to work effectively, potency, pharmacokinetics, and toxicity must interact.…”
Section: Admet Analysismentioning
confidence: 99%
“…The relation between potency, pharmacokinetics, and toxicity is very crucial for the drug efficiency. Using pkCSM [48], Swiss ADME [49], and Data Warrior [48,50], the pharmacokinetics (absorption, distribution, metabolism, and excretion), drug-likeness, and toxicity features of the chemical compound 8 were assessed in this investigation. For a medicine to work effectively, potency, pharmacokinetics, and toxicity must interact.…”
Section: Admet Analysismentioning
confidence: 99%
“…Eg5 inhibitors are characterised by their selectivity and safety, because Eg5 functions only during mitosis; and does not affect the non-proliferative cells, which renders Eg5 inhibitors as selective inhibitors [ 8 ]. In addition, Eg5 does not induce neuropathic side effects, which are found with microtubules inhibitors, due to the absence of the Eg5 protein in the adult peripheral nervous system [ 9 , 10 ]. The literature review revealed that Eg5 inhibitors are divided into two groups, according to their mechanism of action within the Eg5 protein [ 11 ].…”
Section: Introductionmentioning
confidence: 99%